ARABIC LANGUAGE CURRICULUM DEVELOPMENT OF KMI ASSALAM AND ITS CHANGES DURING COVID-19 PANDEMIC - Anshori, A.M. Miftah; Romadhoni, Maria Haniffiah (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
Arabic learning in Assalam Islamic boarding school is an education based on the modern system, this is in relation to the researcher's point of view, the education object, and the content of the types of subjects in the teaching process. This research aims to know the development of the curriculum used in this school and to know the change of the Arabic curriculum during the pandemic covid-19 in this school. This research is qualitative research, and the method of this research is a case study. This research uses observation and literacy study to collect information and data. The results of this research are that Arabic learning in this school is held in many separate subjects, and the learning is based on two main curricula, which is follow the curriculum of the religious ministry and the traditional curriculum (appropriate to the studied books), and in this study includes some information, including the types of curriculum used, the forms of the studied subjects, the method of teaching and the change of Arabic learning during the pandemic covid-19.